ANALISIS PENGARUH LOAN TO DEPOSIT RATIO (LDR) DAN SUKU BUNGA KREDIT TERHADAP SPREAD BASED INCOMEPADA PT BANK RAKYAT INDONESIA (PERSERO) TBK - Rafiuddin Rafiuddin; Ludia Panggalo (JURNAL ULET (Utility, Earning and Tax), 2018)
The aims of this research to determine the effect of loan to deposit ratio and lending rates to spread based income at PT Bank Rakyat Indonesia Persero Tbk. Data were collected using documentation technique. This technique is done by (1) searching internet data by utilizing internet sites to find data used in research, articles, journals and information related to research to strengthen the theoritical foundation, (2) literature study by doing study on reading source and various previous research to know relation between research with previous research. To know the effect of loan to deposit ratio and loan interest rate to spread based income using multiple linear regression analysis, coefficient of determine, simultaneous significant test (F statistic test), and parameter and individual significance test (statistic test t) The result of regression test showed that the interest rate of credit had positive and significant effect on income of PT Bank Rakyat indonesia while the loan to deposit ratio (LDR) has a negative but not partially significant effect on the spread based income of PT Bank Rakyat indonesia. Overally, it can be concluded that the loan to deposit ratio (LDR) and lending rates together may effect the spread based income of PT Bank Rakyat indonesia.